Metabolic engineering of Saccharomyces cerevisiae for second generation ethanol from Xylo-Oligosaccharides. - Procópio, Dielle Pierotti (2021)
The expansion of the human population has raised important questions concerned, for example, the need for increasing demand for food, water, energy, as well climate, and environmental damage. The majority of energy sources are from petroleum and the massive production of carbon dioxide from high-energy consumption links to global climate changes. Lignocellulosic residues are attracting increasing interest worldwide as a new energy matrix to replace the usage of fossil resources. In more recent years, the development of metabolic engineering strategies for strain improvement, microbial fermentation by the widely used yeast, Saccharomyces cerevisiae, has taken on a new dimension, providing significant potential for producing advanced biofuels and biochemicals. In the light of these statements, S. cerevisiae strains have been reprogrammed to ferment sugars derived from lignocellulosic materials. However, fermentation of lignocellulosic biomass suggests many challenges, such as the generation of fermentable sugars from lignocellulosic residues requires harsh chemical and physicochemical pre-treatments which would generate various toxic compounds that inhibit the growth of microorganisms which in turn affect the yield of target products, as well as the inability of S. cerevisiae cells to ferment all available sugars from lignocellulosic biomass, which must be addressed to make feasible the industrial production of biofuels and biochemicals. Therefore, in the present Thesis, our goals were addressed to face some of these challenges, including i) to develop an evolved yeast strain which is capable of efficiently ferment xylose, when comparing with its parental strain. An evolved strain was developed, DPY06, which exhibited an increase of 70% on xylose consumption rate at 72h of cultivation in comparison to its parental strain; ii) to expand the capabilities of industrial and laboratory S. cerevisiae strain to utilize plant-derived xylo-oligosaccharides. To achieve this goal, the engineered strain, SR8A6S3-CDT2-GH432/7 was constructed. In cultivations using a hydrolyzed xylan, the ethanol yield was 84% higher for the engineered strain in comparison with its parental strain; iii) screening the best fitness of S. cerevisiae strain against toxic inhibitors in lignocellulosic hydrolysates. This screening was able to reveal the outstanding performance of one of the industrial strains (SA-1) over the strains evaluated; iv) investigating how S. cerevisiae yeast cells respond to the presence of the p-coumaric acid. The dataset obtained indicated important physiological changes in glucose-limited chemostat cultivations in the presence of 7 mM; and v) to investigate a polymer synthesis by xylose-acetate utilizing S. cerevisiae strain when fermenting glucose, xylose, and acetate.